2016
DOI: 10.1172/jci87037
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SHP2 ameliorates the pathogenesis of systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a devastating multisystemic autoimmune disorder. However, the molecular mechanisms underlying its pathogenesis remain elusive. Some patients with Noonan syndrome, a congenital disorder predominantly caused by gain-of-function mutations in the protein tyrosine phosphatase SH2 domain-containing PTP (SHP2), have been shown to develop SLE, suggesting a functional correlation between phosphatase activity and systemic autoimmunity. To test this directly, we measured SHP2 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 83 publications
(112 reference statements)
3
52
1
Order By: Relevance
“…In addition, PE acts as a key positive regulator of ERK1/2 phosphorylation, decreasing PHA‐induced phosphorylation. On the contrary, previous studies have shown that ERK signaling pathway is decreased in T cells from SLE patients, been associated with overactivation of T cells . Our data did not shown this expected decreased expression of ERK pathway, but similar results between patients with SLE and healthy donors, but these discrepancies might be due to the inactive condition of the cohort of patients along with their pharmacological treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, PE acts as a key positive regulator of ERK1/2 phosphorylation, decreasing PHA‐induced phosphorylation. On the contrary, previous studies have shown that ERK signaling pathway is decreased in T cells from SLE patients, been associated with overactivation of T cells . Our data did not shown this expected decreased expression of ERK pathway, but similar results between patients with SLE and healthy donors, but these discrepancies might be due to the inactive condition of the cohort of patients along with their pharmacological treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…21,22 Inhibition of SH2 domain-containing protein tyrosine phosphatase reduces the proliferation of CD4 À CD8 À T cells and decreases the production of IFN-g and IL-17A in lupusprone MRL/lpr mice. 37 In the present study, MK did not affect numbers of CD4 À CD8 À T cells and the production of these cytokines. Dysfunction of Tregs leads to the exacerbation of LN, with a reduction in IL-2 transcription in TMPD-induced LN and in lupus-prone MRL/lpr mice.…”
Section: Discussionsupporting
confidence: 39%
“…Of the 147,111 Immunochip SNPs that passed quality control analyses, only 30% begin or end a CpG site. Although this is a novel SLE association, GRB2 reportedly regulates SHP2 activity2728, a potential contributor to SLE pathogenesis29.…”
Section: Resultsmentioning
confidence: 91%